Doubly bi-allelic variants of MTHFR and MTHFD1 in a Chinese patient with hyperhomocysteinemia and failure of folic acid therapy - Liu, Yu-Xing; Ding, Man-Hua; Sheng, Yue; Sun, Meng-Fei; Liu, Lv; Zhang, Yang (Frontiers in Genetics, 2023)
Background: Hyperhomocysteinemia (HHcy) is a risk factor for thromboembolic disease. Defects in one-carbon metabolism (1-CM)-related genes, such as methylene-tetrahydrofolate reductase (MTHFR) and methylenetetrahydrofolate dehydrogenase, cyclohydrolase and formyltetrahydrofolate synthetase 1 (MTHFD1) can cause HHcy and may also affect the curative effect of folic acid therapy. While the details of mechanisms are yet to be further investigated. Method: We described a Chinese family with hereditary HHcy. The proband suffered from severe thromboembolic disease and was failure of folic acid therapy. Two sons of the proband were diagnosed as HHcy but had successful intervention after folic acid therapy. Whole-exome sequencing (WES) was conducted to evaluate the genetic lesion of this family. Results: A compound-heterozygous variants (a common polymorphism, p.A222V and a novel variant, p.C631*fs*1) of MTHFR gene, and a homozygous missense variant (p.K134R) of MTHFD1 gene were identified in the proband. Two sons with successful intervention were only harbored the homozygous p.A222V variant of MTHFR gene. Conclusions: The clinical manifestations and genetic research confirmed the diagnosis of HHcy and failure of folic acid therapy in the proband caused by doubly bi-allelic variants of MTHFR and MTHFD1 genes. Our study increased understanding of the molecular basis of 1-CM-related gene defects on folic acid therapy in HHcy.